Recruitment APPLICATION AT PT. TRIKOMSEL MULTIMEDIA USING MICROSOFT VISUAL BASIC 6.0 - Nur Afriani Dewinta; Syahril., SKom Syahril., SKom (Jurnal Sistem Informasi, 2008)
In the process of recruiting a company of the most important thing is to choose, selectingand processing each candidate are correct and can be placed directly on the field,experience and education under their control. Lack of awareness of the importance of thedatabase to make all prospective employees who have or have not been processed,causing errors in the selection and processing of repetitive. To be able to make a gooddocumentation of data and run the process according to the procedures in placediperlukanlah an application that can support the smooth process of recruitment.Therefore, the author makes an application writing process entitled Rekrutment At PT.Trikomsel Mulitimedia, which in scientific writing is made by using programminglanguage Visual Basic 6.0 object-oriented in order to be able to utilize existing facilitiesinside the object.